A new model for predicting carbon storage dynamics and emissions related to the waste management of wood products: introduction of the HWP-RIAL model - Király, Éva; Börcsök, Zoltán; Kocsis, Zoltán; Németh, Gábor; Polgár, András; Borovics, Attila (Acta Agraria Debreceniensis, 2023)
The ability of wood products to store carbon allows for their significant contribution to the climate mitigation efforts and the emission reduction commitments set by the EU. In order to optimise the carbon storage capacity of wood products, it is important to take climate mitigation aspects into consideration as much as possible during their production, use and waste management. The aim of this study was to quantify the effects of product development, recycling, and waste management technologies on carbon storage and emissions. In the frame of the ForestLab project, a new model and decision support tool was developed, which is able to predict the duration of carbon storage of wood products and the evolution of emissions from them. The developed HWP-RIAL model (Harvested Wood Product Recycling, Incineration And Landfill model) uses the methodology of the Intergovernmental Panel on Climate Change (IPCC) to calculate emissions, which is also used in the National Greenhouse Gas Inventory report. It combines the IPCC waste model with equations describing the carbon storage and emissions of wood products, and the model is also supplemented with a self-developed recycling and waste routing module. This paper provides insight into the operation of the model by following the life cycle of 200,000 m3 particle board.